IKLAN MEDIA SOSIAL DAN KONSUMERISME MAHASISWA INDEKOS DI PALOPO - Sabaruddin; Efendi P; Agustan; Bunga Risa (SOSIORELIGIUS, 2024)
This research discusses the role of advertising and marketing communication in shaping the consumption culture of boarding house students in Palopo using Jean Baudrillard's consumerism theory. The objectives of this research are: (1) to determine the importance of testimonials or reviews for boarding house students, and (2) to understand the role of advertising in influencing the consumer preferences of boarding house students. This study uses a descriptive qualitative method because the research was conducted in a natural setting. Data collection methods include observation, interviews, and documentation. The data analysis method involves data reduction, data presentation, and drawing conclusions. The total number of informants in this study is four people. The results of the study indicate that: (1) Boarding house students in Palopo require testimonials and reviews when purchasing a product to ensure the product's quality, as students who are mostly far from their families tend to be cautious when buying products online. (2) The presence of advertisements significantly influences the consumer preferences of boarding house students in making purchasing decisions.